Smart Hanger - Sobri, Mohd Faiz Izzudin; Mohd Yusof, Iman Syazwan (2016)
The Smart Hanger project has been designed to move the clothes hanger using the DC Motor. For the success of these projects two sensor has been used, namely Water Sensor and Light Sensor. The purpose of the sensor is to detect whether it is rainy or not rainy and daylight or night respectively. The aim of this project is to help and ease the burden on people to dry their clothes without having to worry if it rains or it was night. This is because, smart clothes hanger is a hanger designed automatically to move in and out of hanger from the mini house built as a temporary protective housing to prevent clothes from getting wet. Smart Hanger will move out of minihouse during the day or not rain while will move into the minihouse during rain or night. Therefore, the main objective of the project which to ease the burden of all households have been achieved with the creation of Smart Hanger project. The result of this project has been measured in two conditions which result is software simulation and hardware implementation result, for software simulation , a result that was measured using a voltmeter and ammeter in ISIS applications have shown that reading is almost equal to the actual reading . For hardware implementation, the result obtain by using a multimeter was slidely decrease with the actual reading may be due to voltage drop cause by the jumper wire .